Linguistic representation of the concept dignity (namys) in the Kazakh language. (Eurasian Journal of Philology Science and Education, 2015)
The article represents investigation of the verbal means of the concept dignity (namys) and its national and cultural peculiarities. The analysis of linguistic means representing the concept dignity (namys) within the anthropocentric paradigm of modern science gives an opportunity to define lingo-cognitive peculiarities of the concept. The concept dignity (namys) is one of the main concepts that form the world outlook of Kazakh people, and it occupies an important place in the mentality of the Kazakh nation. The article shows the correlation of the concept with such moral notions as honor, respect, shame, honesty, humanity. The article also considers the issues related to the interpretation of the term «concept», language representation and methods of its analysis, difficulties connected with the study of the correlation of the national mentality, culture, language and linguistic consciousness. The study of concepts helps to represent the conceptual and linguistic picture of the world, and to define the national specificity.
Keywords: concept; culture; linguistic world image; national peculiarities